Analysing the Impact of International Capital Flows on the Real and Financial Sectors of India. - Jamal, Nazia and Mujoo, Rachna (2014)
Capital flows are significant for a country when the quantum of those flows is high, steady and stable. The international capital flows, whether in the form of FDI or FPI has a potential to contribute in the economic growth and development of an economy. The present study attempts to explain the effects of private capital inflows (CAPF) on some macro economic variables in India using the time series data between1992 to 2012 for the real and financial sectors. The study also tries to analyse trends and composition of net capital flows in India, besides examining the impact of international capital flows on its economic growth, and suggests policy implication thereof. In the present paper an attempt is being made to examine and analyse the relationship between international capital flows and economic growth and development particularly in the context of India.